(untitled) (Minerva, 2017)
This paper describes the different uses of the adverb σχεδόν, which, from its original meaning as an expression of proximity, adopted, in the Classical Period, a focal use, as an approximative adverb, and another one as a discourse marker. In the novel, it functions above all as a focus adverb. When functioning as discourse marker, it works as a pragmatic operator.